Proceedings of the 8th International Conference on Theory and Practice of Electronic Governance 2014
DOI: 10.1145/2691195.2691303
|View full text |Cite
|
Sign up to set email alerts
|

The adoption of "silver" e-Health technologies

Abstract: Our study aims to reveal the factors (and their antecedents) affecting the adoption of technologies for health by senior citizen. In order to achieve a greater generalizability, our model is tested in relation to 4 types of technologies and in different cultural settings.Our research was developed according with a revised TAM model for silver citizens, where most of the variables are derived from an extensive literature review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Keränen et al [ 16 ] analyzed the differences in information and communication technologies use, attitudes, and reasons for nonuse among older adults categorized as physically frail, prefrail, and robust, and they found that older adults with frailty were less likely to use information and communication technologies than robust people. In addition, Buccoliero and Bellio [ 17 ] analyzed the factors that affect the adoption of technologies for health by older adults. Research showed that, in the case of health technologies, frailty negatively affects perceived ease of use (PEOU) and perceived usefulness (PU), PU positively affects behavioral intention to use health technologies, and PEOU negatively affects behavioral intention to use these technologies [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keränen et al [ 16 ] analyzed the differences in information and communication technologies use, attitudes, and reasons for nonuse among older adults categorized as physically frail, prefrail, and robust, and they found that older adults with frailty were less likely to use information and communication technologies than robust people. In addition, Buccoliero and Bellio [ 17 ] analyzed the factors that affect the adoption of technologies for health by older adults. Research showed that, in the case of health technologies, frailty negatively affects perceived ease of use (PEOU) and perceived usefulness (PU), PU positively affects behavioral intention to use health technologies, and PEOU negatively affects behavioral intention to use these technologies [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Buccoliero and Bellio [ 17 ] analyzed the factors that affect the adoption of technologies for health by older adults. Research showed that, in the case of health technologies, frailty negatively affects perceived ease of use (PEOU) and perceived usefulness (PU), PU positively affects behavioral intention to use health technologies, and PEOU negatively affects behavioral intention to use these technologies [ 17 ]. Interestingly, Lee et al [ 18 ] found that adults with frailty were less likely to use web-based health resources than healthy adults, but adults with frailty who used the internet alone or with assistance were more likely to obtain web-based health information and advice.…”
Section: Introductionmentioning
confidence: 99%
“…Yet as Ling has argued in 2008, intimate personal network can act either as a supportive mechanism or a limiting one (Ling, 2008). This set of conditions and context affects ICT adoption in particular and perceptions of digital technologies in general (Buccoliero & Bellio, 2014). As other research indicates, personal values and interests change over the lifetime (B. L. Neugarten, 1996) and personal communication patterns and the use of media evolve as we grow old, as Ling, Bertel, & Sundsoy (2012) have demonstrated in analyzing differences in SMS use between different age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective norm had positively influenced the intention to use in eHealth studies (Alaiad and Zhou, 2014;Zhang et al, 2014;Chang et al, 2015;Jere et al, 2015;Hsieh, 2015aHsieh, , 2015bMalhotra and Galletta, 1999) and Schepers and Wetzels (2007) quantitative meta-analysis discovered that it had positive influence on attitude. A few other studies on eHealth adoption also exhibited positive relationship between subjective norm and perceived usefulness (An, 2005;Kim and Park, 2012;Buccoliero and Bellio, 2014;Ng et al, 2015). Hence, the following hypotheses were developed for this study:…”
Section: Literature Gapmentioning
confidence: 85%
“…People are more likely to accept and use PHR if they believe it to be simple to use PHR if they think it has an easy-to-use interface and is intuitive. In related eHealth studies, perceived ease of use has positive effect on the intention to use (Buccoliero and Bellio, 2014;Rho et al, 2014;Wang et al, 2014;Chang et al, 2015;de Veer et al, 2015;Jere et al, 2015). Furthermore, perceived ease of use boosted users' acceptance level through attitude besides using the mediating effect of perceived usefulness Predicting e-PHR acceptance (Davis et al, 1989;Davis, 1989;Venkatesh and Davis, 2000;An, 2005).…”
Section: Literature Gapmentioning
confidence: 99%